2003
DOI: 10.1038/sj.npp.1300264
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine Reduces Craving for Alcohol: A DRD4 VNTR Polymorphism by Pharmacotherapy Interaction

Abstract: Separate investigations have suggested that olanzapine, a D4 antagonist, decreases craving after a priming dose of alcohol and that the DRD4 variable number of tandem repeats (VNTR) polymorphism influences the expression of craving after a priming dose of alcohol. The present study tested the hypothesis that olanzapine may be differentially effective at reducing cue-elicited craving based on individual differences in DRD4 VNTR in a sample of heavy social drinkers. Participants were randomly assigned to receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(86 citation statements)
references
References 25 publications
4
80
1
Order By: Relevance
“…It is important to note that there are very few published studies that have used such a stringent experimental control in a test of a pharmacological agent that targets alcohol craving. In this study, olanzapine was found to be much more effective at attenuating craving among individuals with the sevenrepeat allele (Hutchison et al, 2003).…”
Section: Introductionmentioning
confidence: 92%
“…It is important to note that there are very few published studies that have used such a stringent experimental control in a test of a pharmacological agent that targets alcohol craving. In this study, olanzapine was found to be much more effective at attenuating craving among individuals with the sevenrepeat allele (Hutchison et al, 2003).…”
Section: Introductionmentioning
confidence: 92%
“…The 48 basepair VNTR in exon 3 of the DRD4 gene was assayed using modifications of previously reported methods (Sander et al, 1997). Participants were grouped by number of repeats in the VNTR by conventional methods with DRD4 long (DRD4L) comprised of those with at least one copy of the 7 or greater repeats, and those in the DRD4 short group (DRD4S) being those who had neither copy being greater than 6 repeats (Hutchison et al, , 2003. All genotyping was performed by technicians blinded to participant characteristics.…”
Section: Candidate Genotypingmentioning
confidence: 99%
“…Laboratory studies of reactivity to associated cues have shown greater subjective urges reported by DRD4L participants compared to DRD4S participants in smoking and alcohol studies (Hutchison, Lachance et al, 2002;Hutchison, McGeary et al, 2002;McGeary et al, 2001), a study of heroin addicts (Shao et al, 2006), and even a study related to food craving (Sobik et al, 2005). Pharmacogenetic studies suggest the differential subjective urge for alcohol may be attenuated by a D4 receptor antagonist relative to active placebo (Hutchison et al, 2003). A behavior economics study found that DRD4L participants valued alcohol more highly than DRD4S participants (Mackillop et al, under review).…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, pharmacogenetic study [13] revealed that urge for drinking can be reduced by a DRD4 antagonist. It was also proposed that DRD4 is a regulator of "cue-elicited craving" and controls this endophenotype at nicotine addiction [13].…”
Section: Discussionmentioning
confidence: 60%
“…Namely, studies about the influence of smoking and alcohol cues on individuals show a greater urge at individuals with DRD4 gene long allele [11,12,26]. In line with this, pharmacogenetic study [13] revealed that urge for drinking can be reduced by a DRD4 antagonist. It was also proposed that DRD4 is a regulator of "cue-elicited craving" and controls this endophenotype at nicotine addiction [13].…”
Section: Discussionmentioning
confidence: 88%